2006
DOI: 10.1080/10915810600959576
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Protection against Lead-Induced Changes in Human Neuroblastoma Cell Cultures

Abstract: The nervous system is the primary target for low-levels of lead (Pb) exposure and the developing brain appears to be especially vulnerable to Pb neurotoxicity. Chronic low-level Pb exposure causes growth retardation and intellectual impairment. In the present study the protective effect of melatonin during exposure to low-levels of Pb in human SH-SY5Y neuroblastoma cell cultures was assessed. The cells were exposed to Pb (0.01 to 10 microM) for 48 h. Pb inhibited the proliferation of neuroblastoma cells signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Significant increase of proinflammatory mediators, such as TNF-α, IL-1β and PGE 2 was observed in the serum. Our data are in concordance with that of Suresh et al (2006) indicating that Pb induced PGE 2 in the hippocampus from Pbexposed rats. In culture system, Pb is able to modulate the expression of TNF-α in glial cells (Cheng et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Significant increase of proinflammatory mediators, such as TNF-α, IL-1β and PGE 2 was observed in the serum. Our data are in concordance with that of Suresh et al (2006) indicating that Pb induced PGE 2 in the hippocampus from Pbexposed rats. In culture system, Pb is able to modulate the expression of TNF-α in glial cells (Cheng et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…1 One of the heavy metals, lead has threatened environment sustainability and our future generations. Although research on lead neurotoxicity has been of interest for many years, [2][3][4][5][6][7] the effects of lead on the expression of MMP2 and MMP9 in the cerebral cortex and hippocampus still need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that early life Pb exposure causes harm to brain development. 5,6 Both MMP2 and MMP9 play a vital role in the central nervous system. However, the potential effect of lead neurotoxicity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our knowledge, it is well known that lead exposure increases the occurrence of cell death via apoptosis, such as neural (Suresh et al, 2006;Chetty et al, 2007), renal (Stacchiotti et al, 2009) and testicular cells (Adhikari et al, 2001;Massanyi et al, 2007). The cellular toxic effect of lead may be mediated by apoptosis.…”
Section: Discussionmentioning
confidence: 99%